Research on Information Coding of Smart Substation Facing "Two Networks Convergence". Issue 1 (April 2021) - Chen, Pan; Xiao, ZhiHong; Yan, Peili; Feng, Teng; Wang, Xiaoming; Wang, Liang
Abstract: With the popularization and application of "Internet of Things" technologies such as equipment online monitoring and intelligent inspection in the field of substation operation and maintenance, the number of subsystems in smart substations has increased rapidly, and the types of information and the amount of information have shown explosive growth. However, due to disorder and irregular expression, the potential value of a large amount of information is difficult to be effectively used. This paper proposes a "system code-device code-information code" information coding technology that serves the operation and maintenance of information equipment to make information orderly and standardized. This technology lays the foundation for quickly and accurately finding the required information, fully mining and effectively using the value of information, strengthening information fusion between subsystems, and realizing digital management and control of substation equipment information.